A Troubled or a Troubling Candidate – Serbian Accession to the EU - Dordević, Vladimir (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
This article analyzes Serbian accession bid to the EU. Although a candidate country as of March 2012, Serbia will have to manage some painstaking reforms before being admitted into the Union. Even if negotiations over Serbian entry start next year, and date of entry negotiations is still unknown, it seems realistic that Serbia will not join the EU by the end of this decade. In that respect, main argument of this article is that Serbian entry to the EU is dependent on the fol¬lowing issues: battling systemic corruption and (organized) crime; relations with Kosovo; and change of political culture.

Artykuł stanowi analizę serbskich dążeń do członkostwa w Unii Europejskiej. Uwzględniąc status Serbii jako państwa kandydującego do Unii Europejskiej od marca 2012 r., władze serbskie są zmuszone przeprowadzić niekiedy bolesne reformy. Nadal nieznana jest data wejścia Serbii do Unii Europejskiej, choć jasne pozostaje, że państwo to nie stanie się członkiem UE przed końcem tej dekady. Uwzględniając powyższe, w artykule wskazano, że wejście Serbii do UE uzależnione jest od: skutecznej walki z korupcją i (zorganizowan¹) przestępczością; relacji z Kosowem ; oraz zmiany kultury politycznej.
Kandydat z kłopotami czyli kłopotliwy kandydat - serbska akcesja do Unii Europejskiej